Using Simulation in Clinical Education: Psoriasis Area and Severity Index (PASI) Score Assessment - El Miedany, Yasser; El Gaafary, Maha; Youssef, Sally; Almedany, Semeh; Palmer, Deborah (Current Rheumatology Reviews, 2016)
Background: The use of simulation-based learning in the medical field has many benefits, including patient safety, health care professional confidence, accelerating diagnostic and therapeutic procedures, meeting the unfulfilled demand for medical personnel, and lowering of medical errors. Developing of interactive learning tools for teaching a simulated clinical case studies program, is highly needed to improve specialist nurses and middle grade health care professionals skills and competency. Aim: Assess the outcomes of a simulated problem-based learning educational activity for scoring the Psoriasis Area and Severity Index (PASI). Methods: 33 training health care professionals took part in the simulation activity. Before commencing the teaching program, every participant answered a pre-simulation activity confidence and competence levels questionnaire. The simulation activity was carried out in 3 phases: Phase 1: interactive instructor-learner format; Phase 2: Peer-led tutorial; Phase 3: completely independent student led learning adopting a “Problem solving” approach. At the end, every participant completed a questionnaire for post-simulation activity confidence and competence levels. Results: The percentage of agreement with the reference PASI score was progressively improving which reflects improvement of the learners’ skills after adopting the repetitive learner engagement approach. All participants expressed positive attitudes toward the simulation-based course. The overall mean for the student satisfaction subscale was 4.33/5, whereas the overall mean for the selfconfidence subscale was 4.15/5. Conclusion: Simulation-based teaching is an effective way to teach health care professionals. This approach led to improving attitudes, behaviors, interaction, confidence and overall performance leading to potential increased patient safety and better clinical outcomes. The next step is to implement simulation-based training effectively and efficiently in standard teaching.
Keywords: Student-led